2020
DOI: 10.14814/phy2.14387
|View full text |Cite
|
Sign up to set email alerts
|

FXR activation promotes intestinal cholesterol excretion and attenuates hyperlipidemia in SR‐B1‐deficient mice fed a high‐fat and high‐cholesterol diet

Abstract: Obeticholic acid (OCA) activates the farnesoid X receptor (FXR) to lower circulating total cholesterol (TC) and high density lipoprotein‐cholesterol (HDL‐C) concentrations and to stimulate fecal cholesterol excretion in mice by increasing hepatic SR‐B1 expression. Here we show that hepatic SR‐B1 depletion by an adenovirus expressing Sr‐b1 shRNA (Ad‐shSR‐B1) attenuated these beneficial effects of OCA in mice on a chow diet. The mRNA levels of ABC cholesterol transporter genes (Abca1, Abcg1, Abcg5, and Abcg8) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…However, compared with the HFC group, SLPs significantly decreased the expressions of NPC1L1, ACAT2 and MTP mRNA in a dose-dependent manner and the protein levels of NPC1L1, ACAT2and MTP were remarkably down-regulated in the HD group, supported by the previous report (29). In addition, our results also indicated that the mRNA of ABCG8 in the HD groups was overexpressed compared with the HFC group, which was consistent with previous report (30). It is established that cholesterol excretion raised by increasing the expression of ABCG8 genes (30).…”
Section: Effects Of Slps On Intestinal Cholesterol Metabolism In Rats...supporting
confidence: 92%
See 1 more Smart Citation
“…However, compared with the HFC group, SLPs significantly decreased the expressions of NPC1L1, ACAT2 and MTP mRNA in a dose-dependent manner and the protein levels of NPC1L1, ACAT2and MTP were remarkably down-regulated in the HD group, supported by the previous report (29). In addition, our results also indicated that the mRNA of ABCG8 in the HD groups was overexpressed compared with the HFC group, which was consistent with previous report (30). It is established that cholesterol excretion raised by increasing the expression of ABCG8 genes (30).…”
Section: Effects Of Slps On Intestinal Cholesterol Metabolism In Rats...supporting
confidence: 92%
“…In addition, our results also indicated that the mRNA of ABCG8 in the HD groups was overexpressed compared with the HFC group, which was consistent with previous report (30). It is established that cholesterol excretion raised by increasing the expression of ABCG8 genes (30). It is well known, in physiological conditions, there are some transport pathways for nutrition and endogenous substances to traverse the intestinal epithelium.…”
Section: Effects Of Slps On Intestinal Cholesterol Metabolism In Rats...supporting
confidence: 91%
“…In the current study, these effects were observed in BS group. On the other hand, FXR activation is shown to be effective in intestinal cholesterol excretion and hyperlipidemia attenuation [50]. It seems that the excretion of intestinal cholesterol may lead to a decrease in blood cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“… 414 In addition, the sterane derivative and farnesoid-X-receptor (FXR) activator obeticholic acid induced Abca1 mRNA levels in vitro in the ileum of Srb1 -deficient C57BL/6 mice. 415 In THP-1 macrophages, the sterane-like maslinic acid induced ABCA1 mRNA levels, paralleled with an increased cholesterol efflux from these cells. 390 Finally, the Salvia miltiorrhiza -derived tanshindiol C was demonstrated to induce peroxiredoxin 1 mRNA ( Prdx1 ) and protein (PRDX1) content in murine RAW264.7 cells.…”
Section: Part I: Status Quomentioning
confidence: 90%
“…Several in vivo studies demonstrated that modulators of ABCA transporters, in particular ABCA1, have systemic effects. 231 , 249 , 250 , 253 , 271 , 275 , 289 , 293 , 297 , 330 , 335 , 344 , 350 , 361 , 362 , 366 , 368 - 370 , 376 , 378 , 383 , 410 , 415 , 417 - 419 , 425 , 431 , 436 , 448 However, the vast majority of these modulators were regulators, 231 , 250 , 253 , 271 , 297 , 330 , 335 , 344 , 350 , 361 , 362 , 366 , 368 - 370 , 376 , 378 , 383 , 410 , 415 , 417 - 419 , 425 , 431 , 436 , 448 specifically inducers, 250 , 253 , 271 , 297 , 330 , 344 , 361 , 362 , 366 , 368 - 370 , 376 , 378 ...…”
Section: Concluding Remarks: Where Do We Go From Here?mentioning
confidence: 99%